Implementasi Chatbot Telegram Interaktif sebagai Asisten Virtual dalam Jual Beli Busana Menggunakan Framework RASA - Muhammad Alfian Syach; Budi Hartono (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
In today's digital era, the use of technology in various fields of life such as economics and commerce is becoming increasingly important. With the development of increasingly advanced technology, it can provide convenience and time efficiency in expanding market coverage. The use of chatbots as information technology has increased rapidly in recent years and is becoming increasingly popular. Chatbot is a computer program designed to simulate conversations with human users via the internet. The implementation of Telegram chatbots can help simplify communication between sellers and buyers and provide product information. The purpose of this study is to identify and analyze factors that influence the effectiveness of using Telegram chatbots in providing information related to buying and selling Fashion and to determine their effectiveness in increasing customer satisfaction. Evaluation of this chatbot was carried out through direct testing with users to assess the level of accuracy of chatbot responses, user satisfaction, and ease of use. The evaluation results showed that the RASA-based Telegram chatbot, which was evaluated using the System Usability Scale method, was able to provide accurate and quite satisfactory responses when used by users.